The Effect of Health Promotion of Animation Videos on Behavior of Prevention of Dengue hemorrhagic Fever In the Work Area of Health Center, Pasar Minggu District South Jakarta City Year 2021 - Aisyiah, Aisyiah; Wowor, Tommy J; Ahufruan, Yakobus (KHD-Production, 2021)
Dengue hemorrhagic fever is one of the leading causes of morbidity and mortality in the community. One of the efforts made in preventing DHF is through various health promotions by providing information and communication. Such as counseling and campaigns, electronic media, print media, and so on to increase knowledge, attitudes, and practices in the community to have awareness in changing and improving their health status. This study aims to determine the effect of health promotion through animated videos on knowledge, attitudes, and practices towards preventing dengue fever in the working area of ​​the Pasar Minggu Subdistrict Health Center. The sample of this study was 56 families, and the sampling was done using the purposive sampling technique. The results showed an increase in knowledge, attitudes, and the practice of preventive measures against dengue fever in the community after being given health promotion in the form of animated videos (P-value < 0.05). Therefore, the importance of health promotion media in changing a person's knowledge, attitudes, behavior, or actions to undergo better health behavior.